Modeling truncated pixel values of faint reflections in MicroED images. Issue 3 (11th May 2016) - Hattne, Johan; Shi, Dan; de la Cruz, M. Jason; Reyes, Francis E.; Gonen, Tamir
Abstract : A procedure is presented to model the truncated low pixel counts in micro‐electron diffraction (MicroED) images. The correction could extend to any conventional macromolecular X‐ray crystallography or X‐ray free‐electron laser measurements. Abstract : The weak pixel counts surrounding the Bragg spots in a diffraction image are important for establishing a model of the background underneath the peak and estimating the reliability of the integrated intensities. Under certain circumstances, particularly with equipment not optimized for low‐intensity measurements, these pixel values may be corrupted by corrections applied to the raw image. This can lead to truncation of low pixel counts, resulting in anomalies in the integrated Bragg intensities, such as systematically higher signal‐to‐noise ratios. A correction for this effect can be approximated by a three‐parameter lognormal distribution fitted to the weakly positive‐valued pixels at similar scattering angles. The procedure is validated by the improved refinement of an atomic model against structure factor amplitudes derived from corrected micro‐electron diffraction (MicroED) images.